O rosto e a roupa: uma leitura dos outdoors de moda em ambientes urbanos - Busato, Cláudia Maria (2008)
This inquiry studies urban communication and its devices of attention. The objects of this investigation are the fashion images printed in banners, billboards, images in buildings and interiors of shopping centers. The current metropolises show off the fact that they have being organized around the production and the seduction for almost two hundred years. In them, it is possible to check that is built a practice of appearances beside the history of the persons and objects. Paradoxically, the metropolises practice ways of removal, at the same time that social movements produce forms of closeness. In that habitat, it was developed the sewing industry and next to it, a demanding and segmented public moved by the novelty. It is also in the same stage, played by beauty and consumption, that the advertisement image explores its appeal to an immediate one. So, contemporary cities so much produce fast-fashion products as much social types here called image-costumer. It is necessary to emphasize that to be delighted before images, depends on the personal capacity of the individual in managing the received data. In this context, different tendencies of reception are shown: some accept in the full text the pretentious images and others seize only the languages proposed by the media. The hypothesis of this inquiry proposes that fashion images fill out individual deficit through the reconfiguration of their symbolic elements. The first symbol of the individual it is the images that he stores in his memory. Since he was born, the individual is enclosed by stimuli, particularly visual stimuli. These symbols that support the individual nowadays they are also explored by advertisement market. In order to understand the dynamic of these events the following objectives are put: 1. to identify in what ways the observer appropriates the fashion images; 2. to investigate the communicative potential of fashion billboard. The connecting thread of this inquiry goes through the reflections of Dietmar Kamper who discusses the technical images; Harry Pross who treats the pragmatic results of the symbolic orders; Baudrillard and Milton Santos, they analyse the mediation of the objects in urban space; Walter Benjamin and George Simmel, they point out the reflexes of urban life on the individuals. There are two the axles of this inquiry, a vertical, which means, a bibliographical lifting and, the other one, horizontal reached through field work. At both, it is valued in which measure they bring near the images of surface of those primary ones filed by the individual in his memory. The images in fashion billboards are objects of specified glances and they contain in its structure an efficient device of attention: the face. In that context, the observer and the image are face to face but the binomial face-clothes, in the billboards, reveals a mechanism of variation. Because in making seeming, simulating, by the use of the garment becomes a way for going out from the boredom, the changing, when the potential is going up in value of transforming stimuli. The communicative strength of the binomial face-clothes rests in the capacity of the individual of turning elements of the memory into realizable objectives. Since, contemporary individual is enclosed of objects and feelings to build a visual identity